2001
DOI: 10.1097/00000658-200102000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Endogenous Nitric Oxide Synthase in Experimental Acute Pancreatitis: Role of Anti-ICAM-1 and Oxygen Free Radical Scavengers

Abstract: ObjectiveTo evaluate, in an experimental model of acute pancreatitis, the impact of nitric oxide on the disease process and the interaction between nitric oxide and oxygen free radicals. Summary Background DataNitric oxide and oxygen free radicals are involved in the pathophysiology of acute pancreatitis. It is well established that oxygen free radicals play an important role in the development of pancreatic cell damage and remote organ failure, but the impact of nitric oxide on the disease process and the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Oxidative stress was documented in pancreatic tissue by detecting generation of ROS with chemiluminescence (Gough et al 1990) or fluorescence (Urunuela et al 2002) and accumulation of products of ROS-mediated lipid peroxidation (Nonaka et al 1989b(Nonaka et al , 1990Guyan et al 1990; Schoenberg et al , 1995Tsai et al 1998;Rau et al 2000) and protein modification (Reinheckel et al 1998), with concomitant depletion of low molecular weight antioxidants (Neuschwander-Tetri et al 1994;Luthen et al 1995;Tsai et al 1998;Schulz et al 1999;Kruse et al 2001;Rau et al 2001;Rahman et al 2004). It was also confirmed by ESR spectroscopy using spin traps (Nonaka et al 1989a).…”
Section: Mechanisms Of Ros and Rns Induced Damage In Pancreatic Acinamentioning
confidence: 97%
“…Oxidative stress was documented in pancreatic tissue by detecting generation of ROS with chemiluminescence (Gough et al 1990) or fluorescence (Urunuela et al 2002) and accumulation of products of ROS-mediated lipid peroxidation (Nonaka et al 1989b(Nonaka et al , 1990Guyan et al 1990; Schoenberg et al , 1995Tsai et al 1998;Rau et al 2000) and protein modification (Reinheckel et al 1998), with concomitant depletion of low molecular weight antioxidants (Neuschwander-Tetri et al 1994;Luthen et al 1995;Tsai et al 1998;Schulz et al 1999;Kruse et al 2001;Rau et al 2001;Rahman et al 2004). It was also confirmed by ESR spectroscopy using spin traps (Nonaka et al 1989a).…”
Section: Mechanisms Of Ros and Rns Induced Damage In Pancreatic Acinamentioning
confidence: 97%
“…On the other hand, inflammatory mediators have the potential to induce NO via the inducible NO synthase (iNOS) [142] and, thus, might induce an imbalance of ET in favor of NO. In line with this, a recent study could demonstrate increased expression of iNOS in necrotizing pancreatitis, which was reduced by radical scavengers and anti-adhesive strategies [143]. High local levels of NO may cause oxidant/cytotoxic effects due to reaction of NO with superoxide anion to form peroxynitrite with the subsequent formation of nitrogen dioxide and hydroxyl radical [136,144].…”
Section: Potential Candidates Mediating Vasoconstriction/vasodilationmentioning
confidence: 69%
“…A study about severe acute pancreatitis has shown a positive correlation between serum NO level and the number of adherent leucocytes [8] . The expression of iNOS is correlated to changes in the pancreatic histomorphology [9][10][11][12] . The expression of iNOS during reperfusion following pancreatic ischaemia contributes significantly to the development of acute pancreatitis [13] .…”
Section: Discussionmentioning
confidence: 99%